An evaluation of the effectiveness of monitoring systems used for the treatment of attention deficit hyperactivity disorder with methylphenidate (Ritalin) in a child psychiatry clinic - Vogel, Wendy Margaret (My University, 2014)
Monitoring the effectiveness of methylphenidate in the treatmert'' of attention-deficit / hyperactivity disorder (ADHD) in children in Johannesburg is based on the Conners’ Teacher's Rating Scale (CTRS) and school reports. This is the first study to examine the monitoring of the use of methybheniaate in the “mainstream” classroom in post-apartheid South Africa. Educations? changes include racial integration, inclusion of children with learning disabilities, children learning in a second language, and very high pupil: teacher ratios. This study evaluates the CTRS filled in by teachers as a measuring tool for the treatment of ADHD with methylphenidate. It also examines the use of psychological subtests for the monitoring of treatment response. Method: 26 children on treatment for ADHD with methylphenidate have been examined in a double blind placebo-controlled crossover trial. Children are monitored with the CTRS and psychological tests. Results: A strong positive correlation with methylphenidate treatment was found on the following CTRS subscales: hyperactivity (p=0,0001), conduct problem (p=Q,0012), and daydream-inattentive (p=0,0004). The psychological subtests are not useful indicators of treatment response. Conclusion: CTRS can be used to monitor treatment of ADHD in the current school setting.